Isolation and Characterization of Novel Huperzine-Producing Endophytic Fungi from Lycopodiaceae Species - Thanh Thi Minh Le; Ha Thanh Pham; Ha Thi Thu Trinh; Hoa Thi Tran; Ha Hoang Chu (Journal of Fungi, 2023)
Huperzine A (HupA) is an important drug for treating Alzheimer’s disease (AD) and is primarily extracted from the Huperzia serrata (Lycopodiaceae). Failures in the chemical synthesis of Hup and in vitro culture have put H. serrata in danger of extinction, and there is a need for an extensive investigation of Hup from alternative perspectives. The aim of this study is to identify endophytic fungi that produce high Hup or simultaneously produce many types of Hup and have high genetic stability derived from other Lycopodiaceae species as a source of materials for natural Hup production. In this work, Hup-producing endophytic fungi were isolated from three species: Lycopodium clavatum, Phlegmariurus squarrosus, and P. phlegmaria. Of these, L. clavatum and P. squarrosus were confirmed as novel sources of Hup-producing fungi. Based on morphological characteristics and nuclear ribosomal DNA ITS sequences, four endophytic fungi Colletotrichum siamense THG1-17, Epicoccum sorghinum THG01-18, Phoma sp. TKH3-2, and Phyllosticta sp. THG2-27 were firstly isolated from these Lycopodiaceae plants, which were capable of simultaneously producing both HupA and HupB, as evidenced by high-performance liquid chromatography analysis. The four strains showed stability in Hup yield over 50 generations of culture with an in vitro storage period of 3 months. These isolated fungi will provide a new source of materials for further research to develop drugs containing HupA as well as HupB for AD treatment in the future.